Relative efficacy of different types of exercise for treatment of knee and hip osteoarthritis: Protocol for network meta-analysis of randomised controlled trials - Goh, Siew-Li; Persson, Monica; Bhattacharya, Archan; Hall, Michelle C.; Doherty, Michael; Zhang, Weiya (BioMed Central, 2016)
Background: “Exercise” is universally recommended as a core treatment for knee and hip osteoarthritis (OA). However, there are very few head-to-head comparative trials to determine the relative efficacy between different types of exercise. The aim of this study is to benchmark different types of exercises against each other through the use of a common comparator in a network meta-analysis of randomised controlled trials (RCTs).